2001
DOI: 10.1038/35079517
|View full text |Cite
|
Sign up to set email alerts
|

Fabry - Perot interference in a nanotube electron waveguide

Abstract: The behaviour of traditional electronic devices can be understood in terms of the classical diffusive motion of electrons. As the size of a device becomes comparable to the electron coherence length, however, quantum interference between electron waves becomes increasingly important, leading to dramatic changes in device properties. This classical-to-quantum transition in device behaviour suggests the possibility for nanometer-sized electronic elements that make use of quantum coherence. Molecular electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
770
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 906 publications
(846 citation statements)
references
References 29 publications
48
770
5
Order By: Relevance
“…3b) confirms the predominant h/e AB and absent h/2e AAS oscillations, implying quasi-ballistic, phase-coherent transport along the device. Quasi-ballistic behaviour is further confirmed by the observation of Fabry-Perot oscillations [22][23][24][25] in similar TI nanowire devices (see Supplementary Fig. 1 and Supplementary Note 1).…”
Section: Aharonov-bohm Oscillations As a Function Of Fermi Energysupporting
confidence: 57%
“…3b) confirms the predominant h/e AB and absent h/2e AAS oscillations, implying quasi-ballistic, phase-coherent transport along the device. Quasi-ballistic behaviour is further confirmed by the observation of Fabry-Perot oscillations [22][23][24][25] in similar TI nanowire devices (see Supplementary Fig. 1 and Supplementary Note 1).…”
Section: Aharonov-bohm Oscillations As a Function Of Fermi Energysupporting
confidence: 57%
“…The theory provides a good fitting of the experimental results. Carbon nanotubes connected to metallic electrodes allow to study many different regimes in mesoscopic electron transport exhibiting either ballistic or diffusive behavior [1,2]; Luttinger liquid features [3], etc. Several experiments [4] have demonstrated that carbon nanotubes weakly coupled to normal leads can also exhibit Coulomb blockade and Kondo effect, i.e.…”
mentioning
confidence: 99%
“…Compared to the more familiar Fabry-Pérot oscillations, 17 Sagnac oscillations are expected to have a much larger period in gate voltage, and, as we show, in noninteracting wires survive to a temperature a factor of v F / u higher than that required to observe Fabry-Pérot oscillations.…”
Section: Discussionmentioning
confidence: 94%
“…ing that Fabry-Pérot oscillations have been observed in nanotubes up to T =10 K, 17 Sagnac oscillations should be observed up to about 70 K in nanotubes, despite the strong interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation